The Impact of Production-Oriented Critical Reading Module (POCReM) on the Critical Reading Ability among Chinese EFL Non-English Major Undergraduates: A Proposal - He Dongmei; Asmaa AlSaqqaf; Wardatul Akmam (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2022)
Literature review related to reading comprehension among English as Foreign Language (EFL) Chinese learners shows that the EFL undergraduates have serious issues in critical reading and lack training on critical reading. Limited research has been carried out as to training this high-level reading ability among Chinese EFL learners. Mastering critical reading ability of analyzing, synthesizing and evaluating the text is necessary to achieve deep comprehension among EFL undergraduates who aspire to learn and be proficient in other languages. Relevant literature suggests that production-oriented activities can provide more opportunities for learners to participate in reading. Due to the lack of relevant research on how to incorporate production-oriented task more effectively into critical reading activities, this empirical study aims to develop a Production-Oriented Critical Reading Model (POCReM) to improve the critical reading ability (CRA) among EFL non-English major Chinese undergraduates (sophomores) at a public university in China. Using an explanatory mixed method design, the study will survey the critical reading difficulties among non-English major sophomores before the start of the 12-week POCReM treatment. A pre-test and post-test will be conducted to examine whether there are any statistically significant differences in the participants’ performance results before and after the treatment. A semi-structured interview will also be carried out to elicit the participants’ perceptions towards the POCReM intervention. Both qualitative and quantitative data will be examined and analyzed accordingly.